Kajian Risiko dan Mitigasi Bencana Pada Kawasan Pesisir Kecamatan Mangarabombang - Ahmad Fauzi Budjang; Abdul Rachman Rasyid; Sri Aliah Ekawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2021)
An area has the potential for disasters that can have negative impacts, such as losses and casualties. This study aims to assess the level of disaster risk and formulate disaster mitigation directions. The location of this research is in the coastal area of ​​Mangarabombang District. This research was conducted in June-August 2020 (3 months). There are two types of data needed in this study, namely secondary data (data on disaster threats, demographics, and land cover obtained through agency visits) and primary data (data on land prices and area capacity obtained through observation, interviews, and documentation). The analysis used in this research is the analysis of the level of disaster risk by calculating the level of threat, vulnerability and capacity as well as a synthesis analysis of the literature review to determine the direction of mitigation. The results of this study are in the form of a level of disaster risk consisting of low, medium, and high classes. The high level of risk is tsunami, abrasion, and extreme waves. For the level of risk for moderate disasters, namely floods and extreme weather, while for the low risk level, namely earthquakes. Disaster mitigation directions are adjusted to the level of risk which consists of structural and non-structural mitigation. For structural mitigation, namely the provision of tsunami shelters, planting of mangroves and coastal forests, construction of wells and rainwater infiltration drainage, construction of coastal protection, provision of early warning systems, and application of earthquake resistant buildings. For non-structural mitigation, namely increasing the capacity and preparedness of the community and the establishment of a disaster risk reduction forum.